Determining the Apoptotic-Inducing Property of Isothiocyanates Extracted from Three Cultivars of Raphanus sativus Linn. Using the Comet Assay - Maria Carmen S. Tan, Ma. Luisa D. Enriquez & , Rechel G. Arcilla, Marissa G. Noel (Journal of Applied Pharmaceutical Science, 2017)
The apoptotic inducing property of three cultivars of Raphanus sativus L.: white or daikon, red or cherry belle, and large red, were tested on three cancer cell lines: MCF-7, K562, and HT-29. The wild type PAE cells were also incubated with radish extracts for genotoxicity. Each cell line was cultured and treated with either one kind of juice extract or enzymatically hydrolyzed radish sample for 24 hours before harvesting and processing for single cell gel electrophoresis. For each culture set-up, 50 images of cells were captured and analyzed for DNA damage based on three parameters: tail length (TL), percent DNA in the tail (D), and tail moment (TM). Multiple comparisons using Tukey’s HSD procedure showed that juice extracts resulted to substantial genotoxicity in MCF-7 cells among the cancer lines based on the superior TL, D, and TM of the comets having 95% CI of [161.16, 231.44], [33.85, 46.63], and [99.97, 157.91], respectively. The juice extracts exhibited no genotoxicity towards normal PAE cells. Extracts from a β-thioglucosidase assisted hydrolysis of white tubers manifested significant disruption of DNA integrity of MCF-7 cells than that of the red tubers (p < 0.0001). Furthermore, DNA fragmentation for MCF-7 cells treated with juice and semi-purified preparations of the white tuber were found to be similar with 95% CI for mean differences of [-112.81, 24.21] for TL, [-18.03, 5.93] for D and [-56.72, 52.15] for TM. From the results, it can be construed that preparations of R. sativus L. can be a substantial source of biologically active constituents that have the ability to cleave DNA in mutant cell lines while being non-genotoxic to wild type immortalized cells.
Keywords: Raphanus sativus L., comet assay, genotoxicity, glucosinolates, isothiocyanates, immortalized cell lines: HT-29, K562, MCF-7, PAE.